Improving Student’s Creative Thinking Skills using the Case Based Learning (CBL) Model assisted by Virtual Laboratory Media on Optical Materials - Muhyi, Abdul; Windrawan, I Gede; Astra, I Made (Universitas PGRI Semarang, 2024)
Abstract. The research aimed to assess the improvement of students' creative thinking skills through the implementation of the Case Based Learning (CBL) model, supported by a Virtual Laboratory, in the topic of Optics. The method used was Classroom Action Research (CAR) involving 41 students from class XI MIPA 6 at SMA Negeri 6, Kabupaten Tangerang. The research was designed in three cycles, each consisting of four stages: planning, action, observation, and reflection. The results indicated that the application of the CBL model, assisted by the Virtual Laboratory, significantly enhanced students' creative thinking abilities. The average percentage of students categorized as